2019
DOI: 10.3390/microorganisms7060166
|View full text |Cite
|
Sign up to set email alerts
|

Different Secondary Metabolite Profiles of Phylogenetically almost Identical Streptomyces griseus Strains Originating from Geographically Remote Locations

Abstract: As Streptomyces have shown an outstanding capacity for drug production, different campaigns in geographically distant locations currently aim to isolate new antibiotic producers. However, many of these newly isolated Streptomyces strains are classified as identical to already described species. Nevertheless, as discrepancies in terms of secondary metabolites and morphology are possible, we compared two Streptomyces strains with identical 16S rRNA gene sequences but geographically distant origins. Chosen were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
5
23
0
1
Order By: Relevance
“…It is known that the sensitivity to antifungal components between isolates belonging to different species could be different 20. In accordance, the obtained results confirm the assumption that inhibition of tested phytopathogenic isolates is the result of synergistic action of diverse antifungal compounds produced by S. hygroscopicus 21.…”
Section: Resultssupporting
confidence: 88%
“…It is known that the sensitivity to antifungal components between isolates belonging to different species could be different 20. In accordance, the obtained results confirm the assumption that inhibition of tested phytopathogenic isolates is the result of synergistic action of diverse antifungal compounds produced by S. hygroscopicus 21.…”
Section: Resultssupporting
confidence: 88%
“…However, recent studies have found that discrepancies in terms of chemical and morphological features were possible in microorganisms belonging to same taxonomy, as determined for identical 16S rRNA gene sequences 54 . This finding was especially observed when studying bacteria from geographically distant origins or associated with different host species, in accordance to the ecovar concept [55][56][57] . Therefore, although the limitations of 16S rRNA gene have been widely recognized for screening of bioactive strains, we have assumed that the rhizosphere of D. antarctica could lead to high grade of specialism, with a lot of clonal populations.…”
Section: Discussionsupporting
confidence: 61%
“…Despite most of the smBGCs being conserved among the closely related S. venezuelae strains, the production of specific secondary metabolites—chloramphenicol and jadomycin—differed among the strains. The different secondary metabolite profiles of phylogenetically close strains were also reported in two S. griseus strains, which produced seven or four detectable strain-specific secondary metabolites [ 60 ]. By comparing the smBGCs sequences from the closely related strains, we revealed that ATCC 21113 could not produce chloramphenicol due to the single nucleotide deletion in the cmlI gene.…”
Section: Discussionmentioning
confidence: 96%